Type 1 fimbrial phase variation in multidrug-resistant asymptomatic uropathogenic Escherichia coli clinical isolates upon adherence to HTB-4 cells - Ghosh, Arunita; Mukherjee, Mandira (Folia microbiologica, 2024)
The adherence of bladder uroepithelial cells, subsequent expression, and regulation of type 1 fimbrial genes (key mediator of attachment) in clinical multidrug-resistant uropathogenic Escherichia coli (MDR-UPECs) isolated from individuals with asymptomatic bacteriuria (ABU) remain unexplored till date. Therefore, this study aimed to investigate the underlying molecular mechanisms associated with the adherence of clinical MDR-ABU-UPECs to human a uroepithelial cell line (HTB-4), both in the absence and presence of D-Mannose. These investigations focused on phase variation, expression, and regulation of type 1 fimbriae and were compared to a prototype ABU-strain (E. coli 83972) and symptomatic MDR-UPECs. Discordant to the ABU prototype strain, MDR-ABU-UPECs exhibited remarkable adhesive capacity that was significantly reduced after D-mannose exposure, fairly like the MDR symptomatic UPECs. The type 1 fimbrial phase variation, determined by the fim switch analysis, asserted the statistically significant incidence of "both OFF and ON" orientation among the adherent MDR-ABU-UPECs with a significant reduction in phase-ON colonies post-D-mannose exposure, akin to the symptomatic ones. This was indicative of an operative and alternating type 1 fimbrial phase switch. The q-PCR assay revealed a coordinated action of the regulatory factors; H-NS, IHF, and Lrp on the expression of FimB and FimE recombinases, which further controlled the function of fimH and fimA genes in ABU-UPECs, similar to symptomatic strains. Therefore, this study is the first of its kind to provide an insight into the regulatory crosstalk of different cellular factors guiding the adhesion of ABU-UPECs to the host. Additionally, it also advocated for the need to accurately characterize ABU-UPECs.
Keywords: Mannose; infekce vyvolané Escherichia coli; Escherichia coli Infections; proteiny z Escherichia coli; Symptomatic uropathogenic Escherichia coli; Type 1 fimbrial phase variation; Humans; Adhesins, Escherichia coli; mnohočetná bakteriální léková rezistence; mannosa; Fimbriae, Bacterial; epitelové buňky; lidé; Bacterial Adhesion; Escherichia coli Proteins; Drug Resistance, Multiple, Bacterial; regulace genové exprese u bakterií; buněčné linie; Bacteriuria; uropatogenní Escherichia coli; bakteriální adheze; adheziny Escherichia coli; proteiny fimbrií; Cell Line; Epithelial Cells; Type 1 fimbriae-regulating factors; Uropathogenic Escherichia coli; bakteriurie; FimBE recombinases; Gene Expression Regulation, Bacterial; Adhesive capacity; Fimbriae Proteins; bakteriální fimbrie; Asymptomatic uropathogenic Escherichia coli